The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/apm.13092
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinvasive potential of SARS‐CoV2 with neuroradiological and neuropathological findings: is the brain a target or a victim?

Abstract: Coronaviridae family includes pathogen viruses for humans, that lead to clinical conditions with main respiratory involvement; many of these viruses have notoriously a neuroinvasive potential, as demonstrated by published data on SARS‐CoV and MERS‐CoV epidemics, as well by results obtained in experimental models. During pandemic of coronavirus disease 2019 (COVID‐19), it is noticed that the central nervous system involvement represented a truly significant moment in the history of some COVID‐19 patients; indee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 110 publications
(153 reference statements)
0
19
0
Order By: Relevance
“…In this sense, the virus could penetrate the CNS through the neuroepithelium of the olfactory mucosa to reach the olfactory bulb, gain access to the mitral cells and the olfactory nerve, and then spread to adjacent areas of the brain such as the hippocampus and other brain structures [53,54]. This route was demonstrated in mice with intracranially inoculated SARS-CoV-1 and was supported by anosmia as one of the early symptoms in COVID-19 infection [3,5,54]. As previously mentioned, ACE2 and TMPRSS2 have been detected in the nasal mucosa; however, reports demonstrated that they are rather localized to epithelial cells (sustentacular cells) and not in the olfactory neurons [55].…”
Section: Possible Mechanisms Underlying Sars-cov-2mediated Neurological Injurymentioning
confidence: 94%
See 2 more Smart Citations
“…In this sense, the virus could penetrate the CNS through the neuroepithelium of the olfactory mucosa to reach the olfactory bulb, gain access to the mitral cells and the olfactory nerve, and then spread to adjacent areas of the brain such as the hippocampus and other brain structures [53,54]. This route was demonstrated in mice with intracranially inoculated SARS-CoV-1 and was supported by anosmia as one of the early symptoms in COVID-19 infection [3,5,54]. As previously mentioned, ACE2 and TMPRSS2 have been detected in the nasal mucosa; however, reports demonstrated that they are rather localized to epithelial cells (sustentacular cells) and not in the olfactory neurons [55].…”
Section: Possible Mechanisms Underlying Sars-cov-2mediated Neurological Injurymentioning
confidence: 94%
“…Coronavirus disease 2019 (COVID- 19) is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [2]. Although the involvement of the respiratory system is the most relevant clinical feature in COVID-19 patients, systematic reviews with meta-analysis demonstrate that the spectrum of clinical presentations is wider [3]. It has been reported that some severely affected patients experience neurological symptoms like headache, dizziness, and impaired sensorium while recent reports have noted that anosmia, ageusia, ataxia, and seizures may be early signs and symptoms in SARS-CoV-2-infected patients, suggesting that this virus may also be neurotropic [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another relevant concern regards the sampling. It is often unclear if it has been sufficient and if standard protocols have been adopted; therefore, the microscopic results obtained may not be comparable [47]. Furthermore, data appear to be heterogeneous since only a few papers have identified the virus with the reverse transcription-quantitative polymerase chain reaction (RT-qPCR).…”
Section: Autopsy Brain Sampling and Histopathological Assessment In Covid-19 Patientsmentioning
confidence: 99%
“…Furthermore, data appear to be heterogeneous since only a few papers have identified the virus with the reverse transcription-quantitative polymerase chain reaction (RT-qPCR). Even when the assay was executed, it is also uncertain whether the genome could be exclusively identified with that of SARS-CoV-2 [47].…”
Section: Autopsy Brain Sampling and Histopathological Assessment In Covid-19 Patientsmentioning
confidence: 99%